High‐Efficiency Inverted Perovskite Solar Cells via In Situ Passivation Directed Crystallization - Huang, Yanchun; Yan, Kangrong; Wang, Xinjiang; Li, Biao; Niu, Benfang; Yan, Minxing; Shen, Ziqiu; Zhou, Kun; Fang, Yanjun; Yu, Xuegong; Chen, Hongzheng; Zhang, Lijun; et al. (Advanced materials (Weinheim), 2024)
Lead halide perovskite solar cells (PSCs) have emerged as one of the influential photovoltaic technologies with promising cost‐effectiveness. Though with mild processabilities to massive production, inverted PSCs have long suffered from inferior photovoltaic performances due to intractable defective states at boundaries and interfaces. Herein, an in situ passivation (ISP) method is presented to effectively adjust crystal growth kinetics and obtain the well‐orientated perovskite films with the passivated boundaries and interfaces, successfully enabled the new access of high‐performance inverted PSCs. The study unravels that the strong yet anisotropic ISP additive adsorption between different facets and the accompanied additive engineering yield the high‐quality (111)‐orientated perovskite crystallites with superior photovoltaic properties. The ISP‐derived inverted perovskite solar cells (PSCs) have achieved remarkable power conversion efficiencies (PCEs) of 26.7% (certified as 26.09% at a 5.97 mm2 active area) and 24.5% (certified as 23.53% at a 1.28 cm2 active area), along with decent operational stabilities. An in situ passivation (ISP) method is introduced to adjust the crystal growth kinetics and obtain the (111)‐orientated perovskite films with the passivated boundaries and interfaces, leading to high‐performance inverted perovskite solar cells, with power conversion efficiencies (PCEs) of 26.7% (certified as 26.09% at a 5.97 square millimeters active area).